Antioxidant and Cytotoxicity Activities of the Fermentation Extract of the Endophytic Fungi from the Marine Biota of Colt Coral - Dede Sukandar; Nina Artanti; Ika Restu Purwanti; Tarso Rudiana; Fitriyanti Fitriyanti (ALCHEMY:Journal of Chemistry, 2021)
Indonesia has the largest and most biodiverse coral reef in the world. Colt coral has not been studied and explored especially endophytic fungi associated with the coral. Endophytic fungi are highly potential for the production of antioxidant and anticancer compounds. This research aimed to study the antioxidant and cytotoxic activities of fermentation extract from endophytic fungi from colt coral. Filtrate and mycelium extracts were obtained from static and shake fermentations of isolate SKF 15. Antioxidant and cytotoxic assays were conducted by free radical scavenger 1,1-diphenyl-2-picrylhydrazyl (DPPH) and AlamarBlue methods, respectively. The result showed that FD extract provided the highest antioxidant activity with inhibition of 49.36% at 200 ppm of DPPH. Variation of fermentation time (3-21 days) demonstrated the highest activity with inhibition of 66.97% for antioxidant assay (7 days) and 81.13% for cytotoxic assay (3 days). FTIR analysis presented the existence of hydroxyl groups O-H (3452.58 cm-1), C=C groups (1668.43 cm-1); C-O hydroxyl group (1230.58 cm -1), and C-H sp3 groups (2941.44 cm-1). Based on LC-MS analysis, FD extract has a mass of m/z 305.63, [M+H]+, predicted as dihydroquercetin (C15H24O7). Keywords: Antioxidant assay, cytotoxic assay, endophytic fungi, colt coral, DPPH method, AlamarBlue method